2022
DOI: 10.1002/pat.5952
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing of polypropylene micro and nano composites through fused filament fabrication for automotive repair applications

Abstract: The emerging Additive manufacturing technologies are being adopted by different industries, which require developing new materials and procedures. Here we report the development of polypropylene (PP) based composite materials for fused filament fabrication (FFF) process with the aim of enabling fully automatic robotic repair application of plastic components in automotive industry. A key challenge in repair and joining of polyolefins, which are widely used in such applications, is understanding the interplay o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 49 publications
(88 reference statements)
1
15
0
Order By: Relevance
“…It could print non‐periodic 3‐D geometry, large‐scale contiguous parts, multiple smaller distinct parts, or a combination of both with different shapes and sizes on the same machine. Jahromi et al 145 created PP‐based composites with carbon black (CB), ethylene propylene diene monomer (EPDM), and polyisobutylene (PIB), resulting in composite materials that are ideal for additively repairing complex geometries in the automotive industry. The results indicated that the infusion of 10 wt% CB improved the impact strength and storage modulus by 62% and 20%, respectively.…”
Section: Fused Deposition Modelingmentioning
confidence: 99%
“…It could print non‐periodic 3‐D geometry, large‐scale contiguous parts, multiple smaller distinct parts, or a combination of both with different shapes and sizes on the same machine. Jahromi et al 145 created PP‐based composites with carbon black (CB), ethylene propylene diene monomer (EPDM), and polyisobutylene (PIB), resulting in composite materials that are ideal for additively repairing complex geometries in the automotive industry. The results indicated that the infusion of 10 wt% CB improved the impact strength and storage modulus by 62% and 20%, respectively.…”
Section: Fused Deposition Modelingmentioning
confidence: 99%
“…It has been compounded with ceramics, 67,86 natural reinforcements, 98,162 glass fiber, 131,148,149 carbon fiber, 163 and carbon black. 176 On the other hand, PETG has been more frequently reinforced with carbonaceous components 95,104,110,124,131,132,177 and has composed the first successful introduction of metal alloy micro-fibers in additive manufacturing of thermoplastics. 112 With more restricted publication numbers, composites based on high-density polyethylene (HDPE) and polycarbonate (PC) have been explored with ceramic reinforcements 69,77,86,96,160 and carbon fiber, 147 while thermoplastic polyurethane (TPU) has usually been associated with investigations in which flexibility is desired, including the development of electrically conductive composites, 175 the applicability in piezoresistive sensors, 129 and the design of humidity-responsive structures.…”
Section: Adopted Materialsmentioning
confidence: 99%
“…84,87 In the former case, filler weight fractions up to 10% reduced the intrinsic warpage of the polymeric matrix and increased the storage modulus and impact strength of the printed specimens. 176 On the other hand, the latter scenario was primarily concerned with exploring electrical conductivity. From a commercial filament, Tirado-Garcia et al 84 reported a strong influence of printing direction on the thermal, electrical, and mechanical properties of 3D printed PLA/carbon black composites.…”
Section: Matrix/fillermentioning
confidence: 99%
“…The advent of pioneering technologies, such as additive manufacturing and advanced composite materials, is revolutionizing the capabilities of plastics in terms of their structural robustness, operational effectiveness, and overall performance. [25][26][27] This review paper examines the myriad applications of plastics in the automotive industry, exploring current trends and discussing future perspectives. This paper examines the impact of plastics on automobile design, material advancements, sustainability initiatives, and associated challenges within the automotive industry.…”
Section: Introductionmentioning
confidence: 99%
“…In this milieu, a significant surge in the application of plastics in automobiles is expected. The advent of pioneering technologies, such as additive manufacturing and advanced composite materials, is revolutionizing the capabilities of plastics in terms of their structural robustness, operational effectiveness, and overall performance 25–27 . This review paper examines the myriad applications of plastics in the automotive industry, exploring current trends and discussing future perspectives.…”
Section: Introductionmentioning
confidence: 99%